Peningkatan Kemampuan Memahami Teks Biografi Melalui Metode The Learning Cell Pada Kelas VIIID SMP Negeri 6 Wonomulyo Kabupaten Polewali Mandar - Abdul Azis (Fakultas Keguruan dan Ilmu Pendidikan Univ. Al Asyariah Mandar Sulbar, 2018)
This research is based on the problem of the low ability of students to understand biographical texts. The cause of the low ability of students to understand the text is because the learning methods used are still conventional, the implementation of which still takes place in one direction (monotonous), the students are less involved in the learning process, students are only waiting for what is delivered by the teacher. This study aims to describe the ability to understand biographical texts through the Learning Cell method in class VIIID students of Wonomulyo 6th Middle School. The subjects of this study were eighth grade students of SMP Negeri 6 Wonomulyo, Bulo District, Polewali Mandar Regency, 2016-2017 academic year, totaling 27 students. Data collection techniques carried out in this study were Test, Observation and Documentation. The results of the study on students of SMP Negeri 6 Wonomulyo, experienced an increase in this was proven by looking at the results of the research analyzed showed that in the first cycle the average value was 2.40 and experienced an increase in the second cycle with an average value of 3.15. So the use of The Learning Cell method in understanding biographical texts can improve student learning outcomes. In addition, observational data in each cycle showed a change in the attitude of students towards a more positive, both from the attitude of learning, activeness in reading and writing notes, as well as discipline in doing the assignments given.